Habilidades blandas y su influencia en el desempeño laboral del personal del área administrativa del Hospital Napoleón Dávila del cantón Chone - Caicedo Alcívar, Mabel Pierina (2024)
The research was carried out with the purpose of analyzing the soft skills of the public servants of the Dr. Napoleón Dávila Córdova Hospital in Chone canton to determine their influence on job performance, so three stages are developed that correspond to each of them. The specific objectives of the study: in the first stage, the state of the art of soft skills and its influence on the work performance of public servants was established, for which a bibliographic review of the research variables was carried out, later in the second phase A survey structured by the Likert scale was developed, which was validated by the Servqual model, which allowed determining the influence of soft skills on job performance. This was applied to the staff and the results were analyzed using the spreadsheet from Excel; finally, in the third stage, an improvement proposal was developed using the 5W+1H planning matrix, to provide a solution to the shortcomings found. The results demonstrated significant deficiencies in the variables studied, which establishes that soft skills are essential in the job performance of all public servants. In conclusion, this research validates the importance of knowing skills as part of the methods of an organization which generates benefits to the stated objectives.